Conservation of urban environmental corridor in Kuala Lumpur as a method to safeguard the environment - Mohd Shukri, Nur Hannan; Zen, Ismawi (2008)
Today, natural resources in Malaysia has been exploited, networks of roads and railways are laid out, former tin mines are tumed into elite housing, river corridors are getting thinner or turned into monsoon drains and natural swamps are no where to be seen within the city and remnant greiln corridors are decreasing at an alarming rate. The implication of this trend development is the decrease of balance to our cities: the greens provide the habitat for wildlife which plays an important role in supporting the sustainability of man civilization. As more areas are built there is now an imbalance of hard and impermeable surface in the cities, giving rise to hotter urban microclimate - a phenomenon called "heat island". We are now exposed to global warming, flash floods, water and air pollutions, haze, greenhouse effect as well as water shortage. Therefore, it is the need for us, as "Kalifatullah fi 'Ard"(vicegerant of Allah on Earth) to study the implication of the present trend development so that we may able to intervene in a more rational way. A network of well-connected green-corridors is suggested to be a way of reclaiming the environmental balance in the urban areas. These corridors which are termed as urban environmental corridors serve many purposes; most important of which is to provide urban areas with its 'soft elements'. This research is aimed at finding the effectiveness of this approach and how we can adapt it to improve our urban area so that a sustainable approach in development can be achieved.